Chinese Citizen Satisfaction with Government Performance during COVID-19. Issue 132 (2nd November 2021) - Wu, Cary; Shi, Zhilei; Wilkes, Rima; Wu, Jiaji; Gong, Zhiwen; He, Nengkun; Xiao, Zang; Zhang, Xiaojun; Lai, Weijun; Zhou, Dongxia; Zhao, Feng; Yin, Xiufang; et al.
ABSTRACT: While foreign pundits have alternatively blamed and praised the Chinese government's handling of the COVID-19 virus, little is known about how citizens within China understand this performance. This article considers how satisfied Chinese citizens are with their government's performance during the COVID-19 pandemic. It first considers the impact of authoritarian control, political culture, and/or actual government performance on citizen satisfaction. Then, it tests the consequences of satisfaction and specifically whether citizen satisfaction leads to greater trust. Analyzing data from the first post-COVID survey of its kind (n = 19, 816) conducted from April 22 to 28 April 2020, the authors find that Chinese citizens have an overall high level of satisfaction, but that this satisfaction drops with each lower level of government. Further, authoritarian control, political culture, and awareness of government performance all contribute to citizen satisfaction and this in turn, has enhanced public support for the Chinese government.